THE EFFECT OF EDUCATION LEVEL AND EARLY MARRIAGE RATE ON POVERTY: CASE STUDY MADURA ISLAND - Iman Kurniawan; P. S. Prabowo (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
This study aims to analyze the effect of education level and early marriage on poverty in Madura Island covering Bangkalan Regency, Sampang Regency, Pamekasan Regency and Sumenep Regency. This area was chosen because it has the highest percentage of poor people on the island of Madura and even the highest in East Java Province. This study applies quantitative methods with secondary data obtained from the Central Bureau of Statistics of East Java Province. Eviews 10 application as an analytical tool used in this research. The results of this study indicate that the level of education has a negative and significant effect on poverty in all districts in Madura from 2010 to 2019.